The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1016/0014-2999(90)90109-j
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor subtypes in rat pancreatic islets: binding and functional studies

Abstract: Cholinergie agents arepotent modulators of insulin release that aet via musearinie reeeptors. We now investigated the musearlnie receptor subtype present in rat panereatic islets in binding and funetional studies. Binding of 5 nM [ 3 H]N-methylscopolamine ([ 3 H]NMS) was half maximal at 30 min. At 60 min, the maximal total bindingwas 1.29% and the non-specifie binding (presence of 100 ,uM atropine) was 0.18% of the total radioaetivity per 10 f.'g islet protein. The high-affinity Kds were 8.5, 56, 1300 and 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…5), indicating that this response is mediated by the M 3 receptor subtype in WT animals. In agreement with this finding, previous in vitro and in vivo studies using muscarinic antagonists of limited receptor subtype selectivity have also suggested that the M 3 subtype plays a key role in muscarinic receptorϪmediated glucagon release (26,27).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…5), indicating that this response is mediated by the M 3 receptor subtype in WT animals. In agreement with this finding, previous in vitro and in vivo studies using muscarinic antagonists of limited receptor subtype selectivity have also suggested that the M 3 subtype plays a key role in muscarinic receptorϪmediated glucagon release (26,27).…”
Section: Discussionsupporting
confidence: 84%
“…Classic pharmacological studies using different "subtype-preferring" muscarinic antagonists have suggested that the M 3 receptor subtype (previously also referred to as "glandular M 2 receptor subtype") (32) plays a key role in the control of insulin secretion (26,27,32). However, the proper interpretation of these experiments is complicated by the limited subtype selectivity of the muscarinic antagonists used in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium spiny cells in the striatum, motorneurons of the mesencephalon, endocrine cells of the islets of Langerhans in the pancreas, and cells in the islands of Calleja are selectively enriched in m1, m2, m3, and m4 mAChR subtypes, respectively [12,13,20,42]. M35 immunoreactivity was observed in all four areas (Fig.…”
Section: M35 Binding In Rat Cells Enriched In Specific Machr Subtypesmentioning
confidence: 87%
“…Although glucose is the primary physiological trigger and regulator of insulin release, this is also amenable to modulation by the parasympathetic nervous system, which relies mostly on acetylcholine release from islet nerve endings and its binding to specific β-cell muscarinic (M 3 ) receptors (Prentki and Matschinsky, 1987;Verspohl et al, 1990). Cholinergic stimulation of pancreatic β-cells involves phosphoinositide-specific phospholipase C (PLC) activation and the consequent generation of both inositol 1,4,5-trisphosphate (1,4,5-IP 3 ), which triggers Ca 2+ release from internal stores, and 1,2-sn-diacylglycerol (DAG) (Nishizuka, 1986;Wollheim and Biden, 1986), which may lead to the activation of either conventional (i.e., Ca 2+ -and DAG/ phorbol ester-sensitive) or novel (i.e., Ca 2+ -insensitive and DAG/phorbol estersensitive) protein kinase C (PKC) isoforms (cPKC and nPKC, respectively).…”
Section: Introductionmentioning
confidence: 99%